KOMPOSISI JENIS EKOSISTEM MANGROVE DI KAWASAN PESISIR LABUAN KECAMATAN LAGE KABUPATEN POSO - Achmad Rizal (FAPETKAN UNTAD, 2015)
Mangrove ecosystem is vegetation community in tropical coastal area that dominated by various mangrove trees which are having high ability to grow in mud tidal coast. The objective of this research is to assess mangrove species composition in the coastal area of Labuan, Lage, Poso District. The research was conducted from October to December 2011 using line transect with strip sampling applied across topographical contours. The results of the study showed that Rhizophora apiculate has the highest important value index (IVI) for tree level, sapling, seedling with value of 97.3%, 105%, 75%, respectively. With similar calculation, it was recorded that Bruguire gymnorrhiza has the lowest IVI with value of 41.5%, 31%, and 24%, respectively.Key words: Coastal area, composition, mangrove, vegetation.